PENGARUH KOMITMEN PERUSAHAAN, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN - Erina Sovania; Yesaya Setiawan (Value : Jurnal Manajemen dan Akuntansi, 2023)
The development of the automotive industry in Indonesia has become an integral part of the country's economic growth. Along with population growth and increasing people's purchasing power, demand for motorized vehicles has soared, making Indonesia one of the largest automotive markets in Southeast Asia. However, in the midst of this rapid growth, Indonesia is also faced with increasingly fierce competition. This happened to the largest manufacturer in Indonesia, namely Toyota Auto 2000, where there was a decline in sales in the period 2017 to 2023. This research aims to investigate whether company commitment, product quality and service quality have an impact on the sales performance of Toyota Auto 2000, which in the end can create and maintain customer loyalty. The research method applied is a quantitative approach with an explanatory research type, which aims to explore the relationship and impact of the variables studied. The research population consisted of Toyota Auto 2000 consumers in the Bekasi area, with a sample determined based on a formula for a minimum sample size of 10 times the number of indicators used, resulting in a sample of 100 respondents. Data was collected through a questionnaire with a Likert scale as a measurement tool, and data analysis was carried out using the Partial Least Square (PLS) method. The research results show that company commitment and product quality have a significant positive impact on consumer loyalty, while service quality does not have a significant impact on consumer loyalty, which provides important insights regarding aspects that need to be improved in order to overcome declining sales and increase customer loyalty. at Toyota Auto 2000. Keywords: Consumer loyalty, Company commitment, Product quality, Service quality